Hubungan Pelaksanaan Standar Antenatal Care Dengan Kepuasan Ibu Hamil Di Wilayah Kerja Puskesmas Silir Kabupaten Kediri - Cindea, Rienta Wahyu; Sendra, Eny; Hardjito, Koekoeh; Pratamaningtyas, Susanti (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Antenatal care (ANC) services provided according to standards play a crucial role in maintaining maternal and fetal health while simultaneously increasing patient satisfaction. The decline in coverage of K1 and K4 services at the Silir Community Health Center in Kediri Regency emphasizes the importance of evaluating the quality of antenatal care (ANC) services. This study aims to examine the relationship between maternal satisfaction levels and the implementation of ANC standards. This cross-sectional study, using a quantitative analytical approach, involved 45 pregnant women selected using a simple random sampling method. Data were collected through a questionnaire assessing the implementation of ANC standards and patient satisfaction based on the five Servqual dimensions (tangible, reliability, responsiveness, assurance, and empathy). Spearman's test results showed a significant correlation between maternal satisfaction and the implementation of ANC guidelines, according to the Rho test, with a significance value of p = 0.000 (p < 0.05). Most respondents received standard ANC services, although some still complained about long waiting times and lack of communication from health workers. The conclusion of this study confirms that implementing ANC according to procedures has a positive correlation with maternal satisfaction.